Opinions of Users of Psychiatric Services About the Image They Leave on Others and Stigmatizing Terms: Consideration of the Experienced Stigma and Suggestions for Alternative Terms - Dragišić Labaš, Slađana M. (Sociološki pregled, 2019)
This paper considers opinions of users of psychiatric services on how others see them and about the terms used in public discourse for people with mental disorders. Above all, we are interested in terms that the responders deem most appropriate and respectful. In Serbia, this topic remains largely unexplored and is given almost no scholarly attention. The data however indicate that the most commonly used terms are precisely those which are stigmatizing and disqualifying and that the WHO recommendations on the use of different (less stigmatizing) terms has not been followed in all health institutions, and even less so in other institutions or work organizations. Most respondents think that others see them in a negative light, as “dysfunctional”, “oddly behaving and looking”, or even as “dangerous”. We hence present the data on experienced discrimination in work and family environments obtained from two interviews. We believe that, besides the recommendations for the usage of alternative terms, education in educational institutions is needed, as well as well-designed anti-stigma programs and responsible media reporting, and considerably more research in which respondents are persons with mental disorders.Keywords: users of psychiatric services, stigmatizing terms, stereotypes, experienced stigma, change of terms